Pengaruh Choukai Pada Mata Kuliah Nihongo 4 Terhadap Kemampuan Berbicara Bahasa Jepang Mahasiswa Semester IV Di UBINUS - Robihim Robihim (Lingua Cultura, 2007)
Listening is one of four important element in language abillity. By language ability, people can know what the speaking. In the foreign language, listening is very difficult if he don’t know knowlegde about base of foreign languge. Like as foreign language, so do its Japanese language, by continuing practise that one step to try understand vocabulary till step thinking by listening. And then will know how is to speaking some one. And then, after quite and listening, some one can be tell some idea or opinion. And then, practising of listening is need continue for growing up listening ability. In the forth semseter UBINUS, listening is icluding in subjeck of Nihongo IV (Japanese IV) with name sub subject is Choukai (listening).